2022
DOI: 10.1111/1742-6723.13964
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of general practice in reducing emergency department demand: A qualitative study

Abstract: Objective To inform local, state and national strategies intended to reduce demand for ED care, the present study aimed to identify key factors influencing the current provision of acute care within primary healthcare (PHC) and explore the policy and system changes potentially required. Methods Semi‐structured interviews with key stakeholders were audio‐recorded, transcribed verbatim and analysed through content and thematic approaches incorporating the Walt and Gilson health policy framework. Results Eleven i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In the shorter term, the Government has also committed to increasing the number of urgent care centres [ 31 ], however it remains to be seen how these will be staffed. As articulated by Wilson et al, “a whole of system approach” is needed to realign policy priorities in this setting [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the shorter term, the Government has also committed to increasing the number of urgent care centres [ 31 ], however it remains to be seen how these will be staffed. As articulated by Wilson et al, “a whole of system approach” is needed to realign policy priorities in this setting [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of a wide range of interventional approaches to reduce ED use (including health education and PC strengthening, but also quite different measures such as telephone triage and prehospital diversion) has been reviewed,17 18 and assessment remains hampered by deficient evidence. It has been repeatedly suggested that strengthening PC by reducing access barriers and promoting care continuity may attenuate the demand for ED services 19–22. Previous investigations of our working group have identified patient education about alternative care options and self-assessment of symptoms, as well as measures to ameliorate PC access problems, as potentially promising interventional gateways 23.…”
Section: Introductionmentioning
confidence: 95%
“…It has been repeatedly suggested that strengthening PC by reducing access barriers and promoting care continuity may attenuate the demand for ED services. 19–22 Previous investigations of our working group have identified patient education about alternative care options and self-assessment of symptoms, as well as measures to ameliorate PC access problems, as potentially promising interventional gateways. 23 However, while motives for visiting EDs have been extensively explored, far less is known about patients’ views on redirection into PC and their openness towards different interventional approaches.…”
Section: Introductionmentioning
confidence: 99%
“…However, many studies called for better enhancing emergency case management at the PHC levels, thus decreasing the load on the emergency department and helping in stabilization and early initiation of diagnosis and management of emergency cases. It is also recommended that more integration between PHC and emergency departments should be planned [ 4 , 7 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%